ANALISIS ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PERUMDA PASAR SEWAKADARMA SEBAGAI PUSAT PEMASARAN UMKM KOTA DENPASAR - Luh Putu Devi Arikayanti; Dewa Ayu Widya Astiti; Putu Wenny Saitri (JUIMA : JURNAL ILMU MANAJEMEN, 2024)
Organizational citizenship behavior(OCB) is behavior shown by employees in concrete actions in the form of completing work beyond the formal obligations set by the company, but can support organizational function effectively and efficiently. The purpose of this study was to determine the effect of organizational culture, organizational commitment and work motivation on OCB. This research conducted at Perumda Pasar Sewakadarma Kota Denpasar with a population of 122 employees. Determining the number of samples was carried out using the slovin formula so that a sample of 94 employees was obtained and the sample determination method used was sample random sampling. Primary data collection was carried out using a questionnaire consisting of thirty-two statement items as measured by a likert scale with five answer choices. Hypothesis testing is carried out using multiple linear analysis techniques consisting of a determination test, t test and f test. The result of this study indicate that organizational culture, organizational commitment and work motivation have a positive and significant effect on OCB at Perumda Pasar Sewakadarma Kota Denpasar. The advice given to company management is to pay attention to statement items on organizational culture variables, organizational commitment and work motivation which have low values and are still below the average variable value.